Modern resonances of Imperial Germany's biological-warfare sabotage campaign, 1915–18. Issue 4 (1st September 2020) - Ewin, Toby
ABSTRACT: This article summarizes published and archival information about Imperial Germany's attempts to infect draft animals in some Allied and neutral countries with anthrax and glanders during World War I. It casts doubt on claims that the Isle of Man was among the places affected. It considers the extent to which contemporary terrorist activity more closely resembles German biological sabotage plots than it does most modern state weapons-of-mass-destruction programs.